(untitled) (JED (Jurnal Etika Demokrasi), 2024)
Pancasila village is a means of application and internalization of Pancasila values that are currently starting to fade in people’s lives. This article aims to formulate strategies and materials to optimize Pancasila villages as a means of ideological resilience. The study used a descriptive qualitative approach, which was conducted in 2 Pancasila villages in Pekanbaru City and Dumai City, Riau Province. Data collection was carried out through observation, interviews and documentation studies and analyzed using the Miles and Huberman model consisting of data collection, data verification and reduction, and drawing conclusions. Data validity testing used data source triangulation techniques. The results of the study found that (1) Pancasila villages have not been running optimally because activities are more directed at infrastructure management but are still not massive in terms of socialization activities of Pancasila values to the community, both formally and informally; (2) the absence of standard materials or curriculum structures for the socialization of Pancasila values carried out by Babinsa so that there are no guidelines for conducting social communication (komsos); (3) Optimizing the role of Pancasila villages can be done through the use of collaboration and digitalization strategies, while in terms of material structure, a comprehensive and codified material structure is required. Pancasila villages as a stronghold of ideological defense have not been running effectively, so a number of future improvement efforts are needed in terms of strategy and material.